Dissociable Networks of the Lateral/Medial Mammillary Body in the Human Brain - Tanaka, Masaki; Osada, Takahiro; Ogawa, Akitoshi; Kamagata, Koji; Aoki, Shigeki; Konishi, Seiki (Frontiers in Human Neuroscience, 2020)
The mammillary body (MB) has been thought to implement mnemonic functions. Although recent animal studies have revealed dissociable roles of the lateral and medial parts of the MB, the dissociable roles of the lateral/medial MB in the human brain is still unclear. Functional connectivity using resting-state functional magnetic resonance imaging provides a unique opportunity to noninvasively inspect the intricate functional organization of the human MB with a high degree of spatial resolution. The present study divided the human MB into lateral and medial parts, and examined their functional connectivity with the hippocampal formation, tegmental nuclei and anterior thalamus. The subiculum of the hippocampal formation was more strongly connected with the medial part than with the lateral part of the MB, whereas the pre/parasubiculum was more strongly connected with the lateral part than with the medial part of the MB. The dorsal tegmental nucleus was connected more strongly with the lateral part of the MB, whereas the ventral tegmental nucleus showed an opposite pattern. The anterior thalamus was connected more strongly with the medial part of the MB. These results confirm the extant animal literature on the lateral/medial MB and provide evidence on the parallel but dissociable systems involving the MB that ascribe mnemonic and spatial-navigation functions to the medial and lateral MBs, respectively.